Maternal immune activation affects socio-communicative behavior in adult rats - Kinga Gzieło; Diana Piotrowska; Ewa Litwa; Piotr Popik; Agnieszka Nikiforuk (Scientific Reports, 2023)
Abstract A wide body of evidence suggests a relationship between maternal immune activation (MIA) and neurodevelopmental disorders such as autism spectrum disorder (ASD). Since social and communicative deficits are included in the first diagnostic criterion of ASD, we aimed to characterize socio-communicative behaviors in the MIA model based on prenatal exposure to poly(I:C). Our previous studies demonstrated impaired socio-communicative functioning in poly(I:C)-exposed adolescent rats. Therefore, the current study sought to clarify whether these changes would persist beyond adolescence. For this purpose, we analyzed behavior during the social interaction test and recorded ultrasonic vocalizations (USVs) accompanying interactions between adult poly(I:C) rats. The results demonstrated that the altered pattern of social behavior in poly(I:C) males was accompanied by the changes in acoustic parameters of emitted USVs. Poly(I:C) males also demonstrated an impaired olfactory preference for social stimuli. While poly(I:C) females did not differ from controls in socio-positive behaviors, they displayed aggression during the social encounter and were more reactive to somatosensory stimulation. Furthermore, the locomotor pattern of poly(I:C) animals were characterized by repetitive behaviors. Finally, poly(I:C) reduced parvalbumin and GAD67 expression in the cerebellum. The results showed that prenatal poly(I:C) exposure altered the pattern of socio-communicative behaviors of adult rats in a sex-specific manner.